UPM honours Abdullah's role in agriculture sector. - New Straits Times,
KUALA LUMPUR: Former prime minister Tun Abdullah Ahmad Badawi was yesterday awarded the Honorary Doctor of Agriculture Development by Universiti Putra Malaysia.